Design of Wireless Remotely Operated Mobile Robot "Line Botic" for Cleaning Solar Panels - Imaduddin, Ilmirizki; Wandanny, Ryoga Lybraocta Putra; Faruq, Moh Agung Amir; Tuzani, Thoriq (BEST, 2023)
In this research, we will design a wireless remotely operator mobile robot 'linesbotic' for cleaning solar panels, using the open loop method, simply an electric motor that works on the principle of two magnetic fields that produce movement. The aim is to be able to produce a force that drives torque. The motor is installed to carry out certain work that requires the right speed and direction of rotation, so that the speed and direction of rotation of the motor can be adjusted in such a way as to suit the intended use of the motor. The results of the design and software testing for each component can work well according to the list of programs that have been created, while for hardware testing with interference conditions from passing vehicles, road lampposts, trees and buildings with an average percentage of 47% can be achieved. running well, and while testing the joystick in the forward position at angular velocity (-0.0) and at linear velocity (1.0), the joystick in the backward position at angular velocity (-0.0) and at linear velocity (-1.0), the joystick in the right position at angular velocity (-1.0) and at linear velocity (-0.0), the joystick is positioned to the left at angular velocity (1.0) and at linear velocity (-0.0).